ENERGY EFFICIENCY IN THE INDUSTRIAL SECTOR: CONCEPTUAL FOUNDATIONS AND EMPIRICAL RESEARCH - Khamdamova Gavkhar Absamatovna (American Journals, 2025)
This article discusses the issues of industrial energy efficiency in modern conditions. Conceptualization of the concept and empirical analysis are carried out. The necessity of improving energy efficiency in the domestic industrial sector is substantiated, which requires a thorough theoretical analysis of the meaning and interrelation of the relevant concepts, as well as studying the current state and forecasting changes in the field of energy efficiency.
Keywords: Efficiency, energy efficiency, industrial energy efficiency, analysis, forecast, sector, economy, technological progress.